Gene Clusters Located on Two Large Plasmids Determine Spore Crystal Association (SCA) in Bacillus thuringiensis Subsp. finitimus Strain YBT-020 - Zhu, Yiguang (Public Library of Science, 2011)
Crystals in Bacillus thuringiensis are usually formed in the mother cell compartment during sporulation and are separated from the spores after mother cell lysis. In a few strains, crystals are produced inside the exosporium and are associated with the spores after sporulation. This special phenotype, named ‘spore crystal association’ (SCA), typically occurs in B. thuringiensis subsp. finitimus. Our aim was to identify genes determining the SCA phenotype in B. thuringiensis subsp. finitimus strain YBT-020. Plasmid conjugation experiments indicated that the SCA phenotype in this strain was tightly linked with two large plasmids (pBMB26 and pBMB28). A shuttle bacterial artificial chromosome (BAC) library of strain YBT-020 was constructed. Six fragments from BAC clones were screened from this library and discovered to cover the full length of pBMB26; four others were found to cover pBMB28. Using fragment complementation testing, two fragments, each of approximately 35 kb and located on pBMB26 and pBMB28, were observed to recover the SCA phenotype in an acrystalliferous mutant, B. thuringiensis strain BMB171. Furthermore, deletion analysis indicated that the crystal protein gene cry26Aa from pBMB26, along with five genes from pBMB28, were indispensable to the SCA phenotype. Gene disruption and frame-shift mutation analyses revealed that two of the five genes from pBMB28, which showed low similarity to crystal proteins, determined the location of crystals inside the exosporium. Gene disruption revealed that the three remaining genes, similar to spore germination genes, contributed to the stability of the SCA phenotype in strain YBT-020. Our results thus identified the genes determining the SCA phenotype in B. thuringiensis subsp. finitimus.